Randomised phase II study of second-line olaratumab with mitoxantrone/prednisone versus mitoxantrone/prednisone alone in metastatic castration-resistant prostate cancer - Hakenberg, Oliver W; Perez-Gracia, Jose Luis; Castellano, Daniel; Demkow, Tomasz; Ali, Tarek; Caffo, Orazio; Heidenreich, Axel; Schultze-Seemann, Wolfgang; Sautois, Brieuc; Pavlik, Ivan; Qin, Amy; Novosiadly, Ruslan D; et al. (European journal of cancer (Oxford, England, 2019)
INTRODUCTION: Platelet-derived growth factor receptor-α (PDGFRα) is expressed in primary prostate adenocarcinoma and in associated skeletal metastases. Olaratumab is a fully human monoclonal antibody that binds PDGFRα and blocks downstream signalling. This phase II study assessed the efficacy and safety of olaratumab in combination with mitoxantrone and prednisone (M/P) versus M/P alone in patients with metastatic castration-resistant prostate cancer (mCRPC) who progressed after docetaxel. METHODS: Patients were randomised to receive 21-d cycles of olaratumab (15 mg/kg, Days 1 and 8) plus mitoxantrone (12 mg/m2, Day 1) and prednisone (5 mg, twice daily) or M/P alone. Progression-free survival (PFS) was the primary end-point. Secondary end-points included overall survival (OS), safety, and circulating tumour cell (CTC) counts. RESULTS: A total of 123 patients were randomised, 63 to olaratumab + M/P and 60 to M/P. Median PFS was 2.3 months for olaratumab + M/P and 2.4 months for M/P (hazard ratio [HR] = 1.29; 95% confidence interval [CI] = 0.87-1.90). Median OS was 14.2 months for olaratumab + M/P and 12.8 months for M/P (HR = 1.08; 95% CI = 0.72-1.61). Both treatment arms had similar toxicity profiles; neutropenia (24% versus 15%), anaemia (13% versus 14%) and fatigue (11% versus 9%) (olaratumab + M/P versus M/P, respectively) were the most common grade ≥3 events. High CTC count was associated with poorer OS in both arms. Patients with very high cell counts (>37 cells/7.5 ml) exhibited improved OS with olaratumab + M/P (interaction P = 0.043). CONCLUSIONS: Olaratumab + M/P had an acceptable safety profile but did not improve the efficacy of M/P chemotherapy. Further study with selected patient populations and earlier in the disease course might be considered.
Keywords: dospělí; metastázy nádorů; Receptor; prednison; Prostatic Neoplasms, Castration-Resistant; mitoxantron; Mitoxantrone; Adult; Prostate cancer; Platelet-derived growth factor alpha; Antibodies, Monoclonal; lidé; Prednisone; Aged, 80 and over; následné studie; míra přežití; Antineoplastic Combined Chemotherapy Protocols; prognóza; protokoly protinádorové kombinované chemoterapie; Antineoplastics; Monoclonal antibodies; Follow-Up Studies; Male; Aged; Olaratumab; Prognosis; Survival Rate; monoklonální protilátky; lidé středního věku; senioři nad 80 let; nádory prostaty rezistentní na kastraci; senioři; mužské pohlaví; Metastatic; Neoplasm Metastasis; Middle Aged; Humans